The effect of consumers' halal awareness toward purchasing imported food products / Nur Farhana Sahat ... [et al.] - Sahat, Nur Farhana; Abdullah, Sakinatul Raadiyah; Fazial, Farahdina; Said, Shahirah; Abdullah, Mohd Muhsinul Nidzam (Research Management Centre (RMC), 2023)
Consumers' halal awareness refers to the level of knowledge and understanding that consumers have about halal products and services. The term halal pertains to goods and services that are deemed permissible and in accordance with Islamic principles and laws. The objective of this study is to examine the level of halal awareness among Muslims, with a particular focus on its significance for Muslim consumers in their decision-making process when purchasing imported food products. Moreover, the present study endeavors to examine the sentiments and actual purchasing behaviour of Muslim food consumers who have previously engaged in the acquisition of imported food products. A survey of 300 Muslim consumers was conducted in accordance with the objective of the study, which was to examine the Muslim consumers' halal awareness and purchase intent regarding imported food products. The examination of research data, regarding normality, reliability, factor analysis, and multiple regression, is conducted utilising the SPSS program. Based on the findings of the analysis, it can be inferred that there exists a significant correlation between consumers' awareness of halal requirements and their inclination to purchase imported food that adheres to halal standards in Malaysia.